2014
DOI: 10.1007/s00277-014-2243-5
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine effectively improves the metabolism and quality of platelet concentrates during storage

Abstract: Human platelets undergo structural and biochemical alternations during storage which are collectively called platelet storage lesion (PSL). PSL is characterized as metabolic and functionally changes. It causes decrease in platelet recovery and survival. Here, we evaluated the effect of L-carnitine (LC) on the metabolism, function, and mitochondrial metabolic activity of platelet during storage. Platelet-rich plasma was used to prepare platelet concentrate (PC) in Iranian Blood Transfusion Organization. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 41 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…WST-1 test was done to unravel the mitochondrial metabolic activity and the survival rate of PLTs during storage. The survival of PLTs was decreased during storage and one of the reasons for this reduction was the production of lactate and reducing the pH (27,28). In this study, the viability was reduced in all the groups during storage time and the highest reduction in viability was observed in PLTs stored at room temperature.…”
Section: Discussionmentioning
confidence: 48%
“…WST-1 test was done to unravel the mitochondrial metabolic activity and the survival rate of PLTs during storage. The survival of PLTs was decreased during storage and one of the reasons for this reduction was the production of lactate and reducing the pH (27,28). In this study, the viability was reduced in all the groups during storage time and the highest reduction in viability was observed in PLTs stored at room temperature.…”
Section: Discussionmentioning
confidence: 48%
“…L‐carnitine also inhibits the apoptosis mediator Caspase‐3, suggesting it could also reduce platelet apoptosis . In vitro studies have found that addition of L‐carnitine to storage media does result in decreased lactate production and glucose consumption, with an associated preservation of pH after 2 to 5 days of storage . This is associated with an improvement in other in vitro markers of platelet function including shape change, HSR, and platelet counts after 5 days of storage, and an improved aggregation response sometime between 2 and 5 days of storage .…”
Section: Liquid Stored Plateletsmentioning
confidence: 99%
“…In vitro studies have found that addition of L‐carnitine to storage media does result in decreased lactate production and glucose consumption, with an associated preservation of pH after 2 to 5 days of storage . This is associated with an improvement in other in vitro markers of platelet function including shape change, HSR, and platelet counts after 5 days of storage, and an improved aggregation response sometime between 2 and 5 days of storage . Therefore, supplementation of platelet storage media with L‐carnitine may be beneficial for platelets stored at RT for longer than 2 days, with maximal benefit seen if RT storage is extended beyond 5 days.…”
Section: Liquid Stored Plateletsmentioning
confidence: 99%
“…Many physiological effects of LC have been shown. Deyhim et al demonstrated that LC as an additive improves the platelet metabolism in maintaining the quality of stored platelet concentrate for platelet transfusion therapy ( 12 ). Hollister et al reported LC leads to a modest decrease in the rate of progression of Alzheimer’s disease ( 13 ).…”
Section: Introductionmentioning
confidence: 99%